2009
DOI: 10.1111/j.1479-828x.2009.01042.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors predicting blood transfusion in caesarean section

Abstract: In the absence of significant risk factors for haemorrhage at CS in a tertiary setting, routine blood type and screen testing does not enhance patient care. In the rare event that a patient without previously identifiable risk factors requires an urgent blood transfusion, O negative blood could be given in the interim pending formal determination of type and cross-match.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 11 publications
4
21
1
Order By: Relevance
“…Our study has shown an overall lower transfusion rate of 0.53% compared to the published literature. Previous studies showed the transfusion rate for cesarean delivery ranging from 1.1% to 7.8% in developed countries and up to 25% in developing countries . The reason for this could be the increased proportion of elective cesarean sections by maternal request, which has led to a high cesarean rate of 54.73%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study has shown an overall lower transfusion rate of 0.53% compared to the published literature. Previous studies showed the transfusion rate for cesarean delivery ranging from 1.1% to 7.8% in developed countries and up to 25% in developing countries . The reason for this could be the increased proportion of elective cesarean sections by maternal request, which has led to a high cesarean rate of 54.73%.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in other research, elective cesarean sections have less risk of requiring blood transfusion. Hence, the overall incidence of blood transfusion for cesarean delivery would be less …”
Section: Discussionmentioning
confidence: 99%
“…Significant predictors of perinatal transfusion were identified by entering candidate risk factors (polyembryony [yes/no], anemia [yes/no], thrombocytopenia [yes/no], preeclampsia [yes/no], placenta previa [yes/no], placental implantation [yes/no], scarred uterus [yes/no], placental abruption [yes/no], residual placenta [yes/no], stillbirth [yes/no], HELLP [yes/no], hemophilia [yes/no], and heart disease [yes/no]) into a stepwise model. These risk factors have been associated with PPH or perinatal transfusion in other studies . We first conducted a series of univariate analyses for each risk factor.…”
Section: Methodsmentioning
confidence: 99%
“…59 As little as 0.35 IU of oxytocin is needed to initiate acceptable uterine tone in 90% of elective cesarean delivery patients. 60 35 Goodnough et al, 38 Ransom et al, 39 Chua et al, 40 Ransom et al, 41 Scavone et al, 42 Weiniger et al, 43 Cambic et al 44 *1 in 4,000 low-risk patients require blood products. 40 †Extra time is needed to discriminate between anti-D antibodies due to RhoGAM and any additional antibodies that could interfere with a type and cross.…”
Section: Stagementioning
confidence: 97%
“…60 35 Goodnough et al, 38 Ransom et al, 39 Chua et al, 40 Ransom et al, 41 Scavone et al, 42 Weiniger et al, 43 Cambic et al 44 *1 in 4,000 low-risk patients require blood products. 40 †Extra time is needed to discriminate between anti-D antibodies due to RhoGAM and any additional antibodies that could interfere with a type and cross. 44 zThe exact number of units determined by a patient-specific assessment of risk for massive blood loss, and institutional resources to rapidly procure additional blood products.…”
Section: Stagementioning
confidence: 97%